Respostas

  • Usuário do Brainly
2013-05-27T21:05:27-03:00

a) Seja \text{x}=(5,1)^{-2}=\left(\dfrac{51}{10}\right)^{-2}

 

Temos que:

 

\text{x}=\left(\dfrac{51}{10}\right)^{-2}=\left(\dfrac{10}{51}\right)^2=\dfrac{100}{2~601}

 

b) Analogamente, façamos \text{y}=(4,125)^{-1}=\left(\dfrac{4~125}{1~000}\right)^{-1}

 

Logo:

 

\text{y}=\left(\dfrac{4~125}{1~000}\right)^{-1}=\dfrac{1~000}{4~125}

 

c) Como antes, temos:

 

\text{w}=(0,25)^{-3}=\left(\dfrac{-25}{100}\right)^{-3}

 

Desse modo:

 

\text{w}=\left(\dfrac{100}{-25}\right)^3=\dfrac{1~000~000}{-15~625}=-64

 

d) Por fim, vemos que:

 

\text{z}=(-0,5)^{-1}=\left(\dfrac{-5}{10}\right)^{-1}=\dfrac{10}{-5}=-2